Cool colored coating and phase change materials as complementary cooling strategies for building cooling load reduction in tropics - Lei, Jiawei (2017)
Cool colored coating and phase change materials (PCM) are two passive cooling strategies often used separately in many studies and applications. This paper investigated the integration of cool colored coating and PCM for building cooling through experimental and numerical studies. Results showed that cool colored coating and PCM are two complementary passive cooling strategies that could be used concurrently in tropical climate where cool colored coating in the form of paint serves as the “first protection” to reflect solar radiation and a thin layer of PCM forms the “second protection” to absorb the conductive heat that cannot be handled by cool paint. Unlike other climate zones where PCM is only seasonally effective and cool paint is only beneficial during summer, the application of the proposed PCM cool colored coating in building envelope could be effective throughout the entire year with a monthly cooling energy saving ranging from 5 to 12% due to the uniform climatic condition all year round in tropical Singapore.